Inputs to the Philippine labor market information system and TESDA's skills anticipation and prioritization of skills requirements framework - Connie Bayudan-Dacuycuy; Ma. Christina F. Epetia; Anna Rita P. Vargas; John Joseph S. Ocbina (Philippine Institute for Development Studies (PIDS), 2024)
In the Philippines, skills mismatch has persisted since the 1970s, when the higher education system produced more college graduates than the economy could absorb. Prolonged skills mismatch can result in adverse outcomes such as lower wages, decreased job satisfaction, diminished productivity, and increased turnover rates for individuals and businesses. Addressing skills mismatch requires a well-operating Labor Market Information System (LMIS). This study is an input to the Technical Education and Skills Development Authority (TESDA) Skills Anticipation and Prioritization of Skills Requirements (SAPSR) Framework. The SAPSR is intended primarily as a reference in identifying skills requirements. Viewing SAPSR as an integral part of the broader LMIS, this study reviews the available data, the requisite analytical capabilities/tools, and institutional arrangements to make SAPSR relevant to stakeholders. This study finds that while the country has valuable data sources relevant to the skills needs assessment initiative and has several LMIs in operation, there are several areas for improvements in data and its collection, capability building, and institutional arrangements. Drawing from the idea that the SAPSR is part of a system that involves the engagement of various players, the recommendations forwarded by this paper do not focus on what TESDA alone can do but on areas for collaboration to make the LMIS and SAPSR sustainably successful. The recommendations focus on the following areas: partnerships and institutional arrangements, skills taxonomy and skills-occupation mapping, use of PSOC (highly disaggregated if possible) in data collection and other skills and labor market initiatives (e.g., PhilJobNet, PESO-Information System, Philippine Skills Framework Initiative), training to harness emerging data sources and conduct qualitative and quantitative methods, dissemination initiatives, and support.
Keywords: 330; TESDA; labor market information system; skills anticipation and prioritization of skills requirements framework; skills need anticipation